2016
DOI: 10.1016/j.matdes.2016.09.063
|View full text |Cite
|
Sign up to set email alerts
|

A composite hydrogel for brain tissue phantoms

Abstract: Synthetic phantoms are valuable tools for training, research and development in traditional and computer aided surgery, but complex organs, such as the brain, are difficult to replicate. Here, we present the development of a new composite hydrogel capable of mimicking the mechanical response of brain tissue under loading. Our results demonstrate how the combination of two different hydrogels, whose synergistic interaction results in a highly tunable blend, produces a hybrid material that closely matches the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 45 publications
2
112
0
Order By: Relevance
“…It is therefore commonly agreed that a deep knowledge of the correlation between brain composition and mechanical properties of the tissue would enable neuroscientists to shed light on how mechanotransduction phenomena contribute to the functioning of the brain. Furthermore, a quantitative assessment of the viscoelasticity characteristics of the different regions of the brain could pave the way for the improvement of computational brain injury models [15], the engineering of brain phantoms for surgical practise [16,17], the design of mechanically matched brain implants [18], and the production of soft substrates that could mimic different mechanical environments for investigations of stiffness-dependent neural stem cell differentiation [19][20][21] and neuronal and glial cell morphology [22]. Yet, at present, the relation between mechanical properties and cytoarchitecture is still largely unknown.…”
mentioning
confidence: 99%
“…It is therefore commonly agreed that a deep knowledge of the correlation between brain composition and mechanical properties of the tissue would enable neuroscientists to shed light on how mechanotransduction phenomena contribute to the functioning of the brain. Furthermore, a quantitative assessment of the viscoelasticity characteristics of the different regions of the brain could pave the way for the improvement of computational brain injury models [15], the engineering of brain phantoms for surgical practise [16,17], the design of mechanically matched brain implants [18], and the production of soft substrates that could mimic different mechanical environments for investigations of stiffness-dependent neural stem cell differentiation [19][20][21] and neuronal and glial cell morphology [22]. Yet, at present, the relation between mechanical properties and cytoarchitecture is still largely unknown.…”
mentioning
confidence: 99%
“…Based on a fully incompressible behaviour (Poisson's ratio of = 0.5) previously found for this material. Sample-platen interfacial friction effects on the results were minimised via attaching PTFE sheets (0.5 mm thickness) on the platens (Forte et al 2016). The PTFE surfaces were also smeared with a silicon oil of 100000 cST (=0.1 m²/s) viscosity .…”
Section: Methodsmentioning
confidence: 99%
“…Especially, it is necessary to carry out the experimental dosimetric verification before radiotherapy treatments, and generally phantoms have been used for the verification because it is difficult to directly measure actual 3D dose distribution at the target volume inside human body. Recent investigations have demonstrated that additive manufacturing enables us to fabricate the desired shape of phantoms (Takeshi et al 2017;Forte et al 2016;Elter et al 2019;Pantelis et al 2018;Leonard et al 2018;Fabian et al 2016). Due to the irradiated regions in polymer gels becoming visibly opaque with absorbed dose, polymer gels have been considered as an alternative to water as material of phantoms.…”
Section: Introductionmentioning
confidence: 99%